THE STUDY OF SOCIOPRAGMATICS IN WORLD AND UZBEKISTAN LINGUISTICS (Universal International Scientific Journal, 2026)
This article analyzes the origins of sociopragmatics, stages of formation, the studyof communication and human speech based on social factors, and sociopragmatic research
Keywords: anthropocentric linguistics; sociopragmatics; pragmatics